Self-efficacy and pain acceptance as mediators of the relationship between pain and performance of valued life activities in women and men with rheumatoid arthritis - Ahlstrand, I.; Vaz, Sharmila; Falkmer, Torbjorn; Thyberg, I.; Björk, M. (Sage Publications Ltd, 2017)
Â© The Author(s) 2016. Objective: To study whether personal factors (self-efficacy and pain acceptance) mediate the relationship between pain and performance of valued life activities in persons with rheumatoid arthritis. Methods: Persons with rheumatoid arthritis for at least four years (n = 737; 73% women) answered a questionnaire measuring self-efficacy, pain acceptance, performance of valued life activities, and self-rated pain. Relationships among these constructs were explored using univariate and multivariate analyses. Structural equation modelling was then used to examine the mediational role of personal factors on the relationship between pain and performance of valued life activities. Results: A direct negative association between pain and performance of valued life activities was identified (Beta =.34, P < .001). This suggests that people with rheumatoid arthritis who had higher levels of pain has increased difficulties in performing valued life activities. Self-efficacy and activity engagement component of pain acceptance mediated the relationship between pain and performance of valued life activities, however the pain willingness component of pain acceptance did not influence participation in valued life activities. Conclusion: These findings highlight the importance of considering personal factors, such as pain acceptance and self-efficacy, in facilitating participation in valued life activities.